(untitled) (Philological Studies, 2019)
The paper aims at presenting the percentage of the use of perfective (PF) vs imperfective (IPF) verbs in imperative in modern Slovene, partially also in comparison with other Slavic languages, Russian in particular. As a source for analysis by means of CQL three coropora of modern Slovene have been used, namely Gigafida, Kres and ssj500k. In regard to all the concordances containing verbs in imperative the percentage of PF is sligthly above 70% vs 25% of IPF (and that of PF/IPF, biaspectual verbs, slightly less than 6%). When negation is present, the scales are turned with percentage of IPF reaching up to 64%, while that of PF is lowered to (for negation in imperative still substantial) 32%. Comparing the present state with that in the Slovene literary language of 16th century no notable differences in the percentage of PF vs IPF in imperative can be found.